Formação continuada de professores da rede pública do estado de São Paulo : curso de extensão para análise de potenciais culturais e adaptação de materiais didáticos - Kovalek, Olena (2017)
After verifying a shortage of teacher qualification courses concerning the cultural contents approach conveyed by foreign language teaching and learning, we decided to design a project for teacher qualification course to deepen this subject. The extension course was outlined for foreign language teachers of Public Schools of São Paulo State, on Saturdays, with bimonthly meetings interpolated between online meetings by Moodle’s platform. Using this platform, an initial survey, a final presentation, a self-evaluation, and recordings (video and audio), we should collect data for this thesis. We intended to observe if the theoretical arguments, during the course, about cultural contents, would motivate the reflection of the participants in the course in relation to implicit cultural contents in textbooks, and practical approach of teachers/participants in foreign language classrooms of cultural contents throughout the textbook’s adaptation used by them. Besides that, for further work we outlined research questions. The theoretical foundation helped us for reflection and for discussion of the obtained data. Therefore, using a historical journey (LARAIA, 1986; AUGER, 2000, 2003; DURANTI, 1997), we observe the development of cultural concept that helped us to answer the first research question. And, we focused on the relevance of development of extension course (CANDAU, 1997; AUGER, 2005; IMBÉRNO, 2009), on intercultural education (AUGER, 2005), and on textbook adaptation (PRABHU, 1998; Tomlinson, 2012). These theories helped us to answer the second research question. We followed the interpretativist-qualitative research (MOITA LOPES, 1994) and the research-action. In general, we concluded that teacher’s awareness on cultural contents, developed on extension course, helped them for the adaptation and/or development of foreign language teaching materials in order to approach “cultural potentials”. The activities developed by the teachers motivated the students to research cultural contents, to engage in cultural reflections and to recognize (or not) the other culture.